Energy and exergy analysis of domestic refrigerators using R152a to replace R134a. (1st March 2022) - Chen, Xinwen; Liang, Kun; Li, Zhaohua; Jiang, Hanying; Xu, Jing
Highlights: R152a and R134a were assessed in an oil-free domestic refrigeration system. The average CoP of R152a is about 26% higher than R134a. The mass flow rate is up to 31% lower in R152a than R134a. The average evaporator pressure drop for R152a is 13% lower than R134a. The average volumetric efficiency of R152a is about 27% higher than R134a. Abstract: R152a has similar thermodynamic properties to R134a and can be used as one of the alternative refrigerants to R134a. However, flammability restricts the use of R152a in conventional domestic refrigerators. The oil-free VCR system allows the elimination of lubricating oil and therefore reduces the refrigerant charge, thus allowing a reasonable level of safety to be achieved with R152a. This study tests the performance of R152a and R134a in an oil-free domestic refrigerator under various operating conditions. The oil-free VCR system is made up of two oil-free linear compressors with strokes of 0–14 mm, a water-cooled coaxial condenser, an expansion valve and an evaporator with an electric heater. The results show that R152a has an average energy efficiency ratio (EER) that is about 26% higher than R134a. Furthermore, the total exergy destruction of R134a is 9% higher than R152a on average due to a higher vapour density. The lower total exergy destruction allows the VCR system using R152a to achieves an exergy efficiency 7% higher than R134a on average. This paper also reports the experimental results of power input, volumetric efficiency, mass flow rate, normalised coefficient of performance (COP) and isentropic efficiency. It can be concluded that R152a can replace R134a in the oil-free domestic refrigerator.